Structural and functional links between capsule and nephrogenic zone in fetal human kidney - Will W. Minuth (Hygeia Press di Corridori Marinella, 2018)
Little attention received developmental aspects of the human kidney during the late phase of gestation. For healthy newborn babies this subject has no further meaning, since nephrogenesis proceeds unnoticed until birth. Upon delivery, morphogenic activity in the nephrogenic zone is waning and progenitor cell niches aligned beyond the renal capsule disappear by an unknown mechanism. However, a comparable but too early degenerative process takes place in the kidneys of preterm and low birth weight babies. Although born in a period of active nephrogenesis, pathological findings show that they evolve to a high incidence oligonephropathy. Regarding this problematic situation, it is necessary to develop concepts for a therapeutic prolongation of nephrogenesis. However, their realization will be difficult. First, many harming molecules and metabolites, related receptors and disturbed pathways on progenitor target cells have to be identified. Due to the lack of an intact vessel system, a site-specific application of drugs is required. Morphological peculiarities of the nephrogenic zone and positioning of niches must be taken into account. Of current interest are cell biological interactions between the nephrogenic zone and the covering capsule. For example, between gestation weeks 32 and 38, an astonishingly big areal expansion of the capsule and the underlying nephrogenic zone in an order of 30% takes place. Data point out that this little-noticed process also has a special meaning for the control of continuation and cessation of nephrogenesis. Thus, the present contribution likes to inform about this network, and it is simultaneously a call for young scientists to start with investigations in a hardly explored claim.